Identification of Giardia lamblia, Entamoeba histolytica and Cryptosporidium sp. in Feces of Diarrheal Patient at Puskesmas Jatinangor, September–November 2012 - Komathi Palani (Althea Medical Journal, 2015)
Background: Diarrhea is one of the main public health problems occurring in West Java. One of the affected areas is Subdistrict Jatinangor. Inappropriate management of sanitation facilities around Jatinangor area causes contamination of water. Cikeruh River is one of the water sources in Jatinangor Area, from which people obtain water for daily activities. Water borne illness due to poor sanitation condition can lead to parasitic infection such as Giardia lamblia, Entamoeba histolytica and Cryptosporidium parvum which can cause a prolonged diarrhea. There has not been any study done regarding the presence of parasitical infection causing diarrhea around Jatinangor.